2014 IEEE 14th International Working Conference on Source Code Analysis and Manipulation 2014
DOI: 10.1109/scam.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Pangea: A Workbench for Statically Analyzing Multi-language Software Corpora

Abstract: Abstract-Software corpora facilitate reproducibility of analyses, however, static analysis for an entire corpus still requires considerable effort, often duplicated unnecessarily by multiple users. Moreover, most corpora are designed for single languages increasing the effort for cross-language analysis. To address these aspects we propose Pangea, an infrastructure allowing fast development of static analyses on multi-language corpora. Pangea uses language-independent meta-models stored as object model snapsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Caracciolo et al (2014) have created a workbench for running analyses on multi-language software systems; Sobernig and Zdun (2010) have addressed the topic of how to evaluate execution speed of cross-language method invocations in Java. Both are thus enablers for future efforts which may go into the directions of tool support or better linking mechanisms we have indicated.…”
Section: Cross-language Linkingmentioning
confidence: 99%
“…Caracciolo et al (2014) have created a workbench for running analyses on multi-language software systems; Sobernig and Zdun (2010) have addressed the topic of how to evaluate execution speed of cross-language method invocations in Java. Both are thus enablers for future efforts which may go into the directions of tool support or better linking mechanisms we have indicated.…”
Section: Cross-language Linkingmentioning
confidence: 99%
“…As such, several studies have investigated the link between identifier naming and code readability and comprehension [2], [5], [24], [26], [27] or identifier naming and externally observable aspects of the software development process that are expected to be affected by comprehension such as change-proneness [1], quality [4], [6] and presence of faults [7], [8]. Caprile and Tonella [29] have observed that names of C functions consist of on average of 2.04-3.36 words, often verbs expressing action, while Caracciolo et al observed that most method names in Java and Smalltalk also tend to consist of several words but rarely more than five words [30].…”
Section: Related Workmentioning
confidence: 99%
“…This corpus contains 810 Java projects, 371,745 Java source files, and 34,894,844 lines of code. We are making the corpus available for download through the Pangea infrastructure 3 [12].…”
Section: A Experimental Corpusmentioning
confidence: 99%